Smoking, hypertension, and colonic anastomotic healing; a combined clinical and histopathological study. Issue 5 (May 1996) - Fawcett, A; Shembekar, M; Church, J S; Vashisht, R; Springall, R G; Nott, D M
Abstract : BACKGROUND--Large bowel anastomotic breakdown occurs as a result of perianastomotic ischaemia. Preservation of the macroscopic arterial supply to the perianastomotic tissues is vital, but little is known about the influence of microvascular disease on anastomotic healing. AIMS--To study the associations between risk factors for macrovascular disease, the presence of colonic microvascular disease, and the incidence of anastomotic dehiscence. PATIENTS--147 consecutive colonic surgery patients. METHODS--The prevalence of smoking, hypertension, diabetes, and ischaemic heart disease were established retrospectively from patient notes. These risk factors were correlated with histopathological assessment of resection margin vasculature and clinical follow up. RESULTS--Smoking and hypertension were significantly associated with an increased incidence of anastomotic dehiscence and microvascular disease. Microvascular disease was positively correlated with an increased incidence of anastomotic dehiscence. CONCLUSIONS--Microvascular disease predisposes to anastomotic breakdown. This effect may in part be due to vasospasm in the diseased vessels, which are hypersensitive to serotonin, a vasoactive amine known to be present in increased quantities in the serum of smokers, hypertensives, and after surgery. Treatment with serotonin antagonists in the perioperative period may be beneficial to anastomotic healing, helping to maintain microvascular flow.